Combining abilities and components of variance for ear height in silage maize - Sečanski Mile; Živanović Tomislav (Selekcija i Semenarstvo, 2007)
The aim of this study was to evaluate the following parameters for the ear height of silage maize: variability of inbred lines and their diallel hybrids, superior-parent heterosis, components of genetic variability, heritability and combining ability on the basis of a diallel set. The two-year four-replicate trail was set up according to the randomized block design in the location of Zemun Polje. The analysis of components of genetic variance for ear height indicates that the additive components (D) were lower than dominant components (H1 and H2) of genetic variance, while the frequency of dominant (u) and recessive genes (v) for this observed trait shows that dominant genes prevailed. The results of the Vr/Wr regression analysis point out to superdominance of ear height inheritance. The analysis of variance of combining abilities shows that there were highly significantly positive values of GCA and SCA for ear height in both years of investigation. Non-additive gene effects played an important role in inheritance of this trait, which was illustrated by the GCS to SCA ratio < 1.